Kedudukan Keuangan Negara Dalam Badan Usaha Milik Negara - Harly Clifford Jonas Salmon (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The state separates its finances to be used as capital in state-owned enterprises. However, Law Number 17 of 2003 concerning State Finances still counts the separated capital as state finance, contrary to the principle that separated finance is corporate finance.Purposes of the Research: Analyzing the Position of State Financial Status in State-Owned Enterprises. Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials carried out in this research is through literature study.Results of the Research: The results of the study show that state finances are all rights attached to the state in the form of money or goods, including equity participation in state-owned enterprises. However, in its management, when the capital has been handed over to a state-owned enterprise, the state's financial status has completely changed to private finance, in this case it is a state-owned enterprise in accordance with Article 4 paragraph (1) UUBUMN which states that the company's capital comes from separated state assets. This capital in the legal context of the company is equity capital. Pursuant to the provisions of Article 1 point 7 of Government Regulation Number 72 of 2016 concerning Procedures for Participation and Administration of State Capital in BUMN and Limited Liability Companies, state capital participation is the separation of State assets from the APBN or determination of company reserves or other sources to serve as BUMN capital and/or other limited liability companies are managed as a corporation. has also been explained in the Constitutional Court Decision No. 77/PUU-IX/2011. The Constitutional Court ruled that a BUMN is a business entity that has separate assets from state assets so that the authority to manage business assets, including the settlement of BUMN debts, is subject to the limited liability company law. This is the point of privatization of state finances which are included in state-owned enterprises where the capital is then managed by the business entity with business principles.